Pencitraan bangsa Jerman dalam novel Generation Golf - Aini, Desti Nur; Syafruddin, Dudy (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This research aims to describe the various stereotypes, prejudices, and ethnocentrism that appear in the characters of the novel Generation Golf. A qualitative approach was applied in this research. The note-reading technique was used for data collection, and the data were analyzed using domain analysis. The results indicate that various forms of stereotypes, prejudices, and ethnocentric attitudes are present. The stereotypes identified include both negative and positive types; the prejudices appear in the form of negative feelings, beliefs, and actions; and ethnocentric attitudes are expressed through the attribution of German culture in comparison with other nations.